Analysing the employability of business and administration study programs in Portugal - Galego, A.; Saraiva, M. (Higher Education of Social Science, 2013)
This paper investigates the impact of institutions and study programs´ characteristics on the employability of higher education graduates. We consider the field of Business and Administration in Portugal, and employ an econometric fractional model to analyse the influence of several indicators in the unemployment “propensity” of the pair study program/institution.The results show important differences between public and private institutions, between study programs of great and small size and among the several fields of graduation within Business and Administration. Moreover, the regional location of the institutions/study programs seems to be important to explain unemployment differences.